Agama dan Ritual Slametan: Deskripsi-Antropologis Keberagamaan Masyarakat Jawa - Kholil, Ahmad (UIN Maulana Malik Ibrahim Malang, 2008)
Substantially, the core of religious belief is believing God as being transcendental, sacred, pure, above everything related to the Almighty. Functionally, the core of religious belief is an effort to handle life problems: existential problems. Religion always leads to goodness physically and spiritually. However, the followers of religion do not always do it. Diversity thought in a religion using charity done by its followers always colors tire practice of the social diversity. It might be caused by a misinterpretation to the doctrine or certain vested interests often happened in the political life. In fact, this is the reality happened in the religious life of our society.